2009
DOI: 10.1021/ol902335c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cross-Coupling Reaction of Secondary Benzylic Bromides with Grignard Reagents

Abstract: A mild palladium-catalyzed Kumada-Corriu reaction of secondary benzylic bromides with aryl and alkenyl Grignard reagents has been developed. In the presence of the Xantphos ligand, the undesired beta-elimination pathway is minimized, affording the corresponding cross-coupling products in acceptable to good yields. The reaction proceeds with inversion of the configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…In 2009, Adrio and Carretero discovered that Grignard reagents were successful coupling partners for the same electrophile, such that the reaction of benzhydryl bromide with 4-fluorophenyl-magnesium bromide gave the corresponding triarylmethane in excellent yield employing a combination of Pd(MeCN) 2 Cl 2 and Xantphos as the catalyst (Scheme 1b). 12 In 2008, the Kuwano group reported that diarylmethyl methyl carbonate was a good alternative to diarylmethyl halides as the electrophile for the production of triarylmethanes (Scheme 2). 13 The carbonate derivatives were reacted with arylboronic acids in the presence of a catalytic amount of [Pd(ally)Cl] 2 with bidentate 1,5-bis(diphenylphosphino)-pentane (DPPPent) ligand and K 2 CO 3 as the base.…”
Section: Synthesis Of Achiral Triarylmethanes Bymentioning
confidence: 99%
“…In 2009, Adrio and Carretero discovered that Grignard reagents were successful coupling partners for the same electrophile, such that the reaction of benzhydryl bromide with 4-fluorophenyl-magnesium bromide gave the corresponding triarylmethane in excellent yield employing a combination of Pd(MeCN) 2 Cl 2 and Xantphos as the catalyst (Scheme 1b). 12 In 2008, the Kuwano group reported that diarylmethyl methyl carbonate was a good alternative to diarylmethyl halides as the electrophile for the production of triarylmethanes (Scheme 2). 13 The carbonate derivatives were reacted with arylboronic acids in the presence of a catalytic amount of [Pd(ally)Cl] 2 with bidentate 1,5-bis(diphenylphosphino)-pentane (DPPPent) ligand and K 2 CO 3 as the base.…”
Section: Synthesis Of Achiral Triarylmethanes Bymentioning
confidence: 99%
“…In many cases, no impact of the purity of the iron source on the catalytic activity was observed [106]. Also, it seems that the Kumadatype cross coupling of Grignard reagents and halides, further discussed by Robin Bedford in [29], is not due to metal contaminants; palladium-catalyzed Kumada reactions appear not to work ligand-free [107][108][109]. The lower efficiency of palladium-catalyzed Kumada-type couplings was attributed to the high reactivity of Grignard reagents compared to the nucleophiles typically employed in crosscoupling chemistry, such as boranes [109].…”
Section: Enantioselective Iron Catalysis and Stoichiometric Consideramentioning
confidence: 99%
“…4-(1-Phenylethyl)anisole (2u): [43] Eluent: hexane/ethyl acetate = 20/1; colorless liquid; yield: 0.148 g (70%). …”
mentioning
confidence: 99%